2003
DOI: 10.1242/dev.00567
|View full text |Cite
|
Sign up to set email alerts
|

Prickle 1 regulates cell movements during gastrulation and neuronal migration in zebrafish

Abstract: During vertebrate gastrulation, mesodermal and ectodermal cells undergo convergent extension, a process characterised by prominent cellular rearrangements in which polarised cells intercalate along the medio-lateral axis leading to elongation of the antero-posterior axis. Recently, it has become evident that a noncanonical Wnt/Frizzled (Fz)/Dishevelled (Dsh)signalling pathway, which is related to the planar-cell-polarity (PCP) pathway in flies, regulates convergent extension during vertebrate gastrulation. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
224
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(241 citation statements)
references
References 68 publications
(71 reference statements)
11
224
2
Order By: Relevance
“…Furthermore, morpholino-mediated knockdown of zebrafish prickle leads to defects in gastrulation-associated cell movements and tangential migration of nVII neurons (Carreira-Barbosa et al, 2003), as demonstrated previously for trilobite. These results suggest that Trilobite and Prickle function in the same pathway and may modulate environmental cues necessary for initiating and/or maintaining nVII neuron migration.…”
Section: Environmental Cues Regulating Bmn Migrationsupporting
confidence: 73%
See 2 more Smart Citations
“…Furthermore, morpholino-mediated knockdown of zebrafish prickle leads to defects in gastrulation-associated cell movements and tangential migration of nVII neurons (Carreira-Barbosa et al, 2003), as demonstrated previously for trilobite. These results suggest that Trilobite and Prickle function in the same pathway and may modulate environmental cues necessary for initiating and/or maintaining nVII neuron migration.…”
Section: Environmental Cues Regulating Bmn Migrationsupporting
confidence: 73%
“…A zebrafish homologue of prickle, which encodes a LIM-domain protein component of the Wnt/PCP pathway, is expressed in r4 and r5 in the vicinity of, but not in, migratory nVII neurons (Carreira-Barbosa et al, 2003). Furthermore, morpholino-mediated knockdown of zebrafish prickle leads to defects in gastrulation-associated cell movements and tangential migration of nVII neurons (Carreira-Barbosa et al, 2003), as demonstrated previously for trilobite.…”
Section: Environmental Cues Regulating Bmn Migrationsupporting
confidence: 59%
See 1 more Smart Citation
“…Removal of Dvl, Vangl and prickle orthologs results in convergent extension defects during neurulation, cochlear formation and gastrulation, indicating that PCP signaling is required for these morphogenetic movements in vertebrates [93][94][95][96][97][98][99]. Cell intercalation has not been demonstrated during the development of the mouse kidney tubules although it does occur during the development of the fly Malpighian tubules [100].…”
Section: Pathway Usage In Renal Vesicle Formationmentioning
confidence: 99%
“…A ''core'' set of PCP genes was established in Drosophila (Fanto and McNeill, 2004). Homologues in vertebrates include Vangl1/ 2, Frizzled3 and 6, Disheveled1-3, Celsr1, Prickle, Scribbled, PTK7, and Ankrd6 (Schwarz-Romond et al, 2002;Carreira-Barbosa et al, 2003;Curtin et al, 2003;Montcouquiol et al, 2003;Lu et al, 2004;Wang et al, 2006a,b;Torban et al, 2007). Examples of PCP can be observed throughout vertebrate embryogenesis, most notably in the convergent extension (CE) movements required to elongate and shape the neural epithelium during early neurulation, as well as the highly organized epithelium within the cochlear sensory structures (Park and Moon, 2002;Wang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%